A more secure world : our shared responsibility : report of the High-level Panel on Threats, Challenges, and Change. (United Nations, 2004)
In his address to the General Assembly in September 2003, United Nations Secretary-General Kofi Annan warned Member States that the United Nations had reached a fork in the road. It could rise to the challenge of meeting new threats or it could risk erosion in the face of mounting discord between States and unilateral action by them. He created the High-level Panel on Threats, Challenges and Change to generate new ideas about the kinds of policies and institutions required for the UN to be effective in the 21 st century. In its report, the High-level Panel sets out a bold, new vision of collective security for the 21 st century. We live in a world of new and evolving threats, threats that.